Disturbed body schema, perceptual body image, and attitudinal body image in patients with borderline personality disorder - Szily, Dorottya; Kelemen, Rebeka; Nagy, Zita S.; Szabó, Dominik; Unoka, Zsolt Szabolcs (Frontiers in Psychiatry, 2023)
Background Borderline personality disorder (BPD) is a severe mental disorder that affects attitudes toward the body. However, whether this condition also affects body schema and perceptual body image remains unclear. Previous questionnaire-based studies found dissatisfaction with one's body in patients with BPD. In addition to attitudinal body image, our study investigates whether body schema and perceptual body image are disturbed in patients with BPD. Method Our study included 31 patients diagnosed with BPD (25 women) and 30 healthy individuals (19 women) (Mage = 29 for both groups). The SCID-5-PD interview was used to determine personality disorder. Attitudinal body image was measured using the Body Attitude Test (BAT) factors. Body schema and perceptual body image were measured by two conditions of a body representation task, the body portraying method (BPM). Results BPD patients achieved higher scores in all three BAT factors and were more susceptible to misinformation in both conditions of BPM. Based on the results, BPD patients appear to have more negative attitudes toward their bodies and worse perceptual body image and body schema. Conclusion The novel finding of our study is that, besides the previously found attitudinal dissatisfaction with the body, individuals with BPD also show disturbances at the levels of body schema and perceptual body image. Our findings concerning disturbances in body schema and perceptual body need further research into their etiological factors and provide new therapeutic targets for the treatment of BPD.